An efficient route for design of luminescent composite materials based on polyethylene containing europium dibenzoylmethanate. (20th October 2017) - Roitershtein, Dmitrii M.; Puntus, Lada N.; Lyssenko, Konstantin A.; Taidakov, Ilya V.; Varaksina, Evgenia A.; Minyaev, Mikhail E.; Gerasin, Victor A.; Guseva, Maria A.; Vinogradov, Alexey A.; Savchenko, Maria S.; Nifant'ev, Ilya E.
Abstract : A Eu-doped luminescent composite material based on polyethylene has been developed and studied by optical spectroscopy, luminescence intensity mapping, and SEM. Abstract : Luminescent composite materials based on linear polyethylene doped by a well dispersed tetrakis dibenzoylmethanate europium complex have been developed. The anion of the latter serves as an efficient light harvesting antenna and possesses the desired photophysical properties. The targeted modification of the Eu complex, namely introduction of a long hydrocarbon chain into the tetraalkylammonium cation [RNEt3 ] +, has ensured the compatibility of the complex with the polyethylene matrix. The [RNEt3 ] + cation has been obtained by using long-chained 1-iodoalkanes synthesized via the Nd-catalyzed ethylene oligomerization process. The photophysical properties and the homogeneity of the obtained composites have been controlled by optical spectroscopy, luminescence intensity mapping as well as scanning electron microscopy.